A Project Feasibility Study on an Herbal Eye Drop Product Nature's Drop - Baqueriza, Nikki Lou (College of Engineering, 2001)
This study aims to determine the feasibility of the manufacturing a new herbal eye drop, Nature's Drop. Nature?s Drop is a new eye drop product that is made from natural ingredients, which come from indigenous sources. The extract is from the leaves of a locally cultivated plant, Calophyllum Inophyllum, locally known as Bitaog, which cures several eye diseases such as conjunctivitis, excessive lacrimation, cloudy eyesight, soothes pain, minor irritations, itch and inflammation and it prevents cataract. Its wider range of uses than the currently available eye drop products and the lower cost that it offers provides a competitive edge needed to establish it In the market. This study is composed of a market study, technical study, financial study, and social profitability study. Based on the results of demand analysis and market segmentation using market determinants such as the prevalence of eye diseases, air pollution level, location ,and age, the target market for the herbal eye-drop is determined. The selected target market includes individuals residing in urban areas specifically Metro Manila where air pollution level is predominant because of industrialization. Results of the Second National Survey of Blindness conducted in 1995, many eye diseases causing monocular blindness (one eye is blind) such as cataract was found to be traceable to industrialization. Demand growth patterns in the market study indicate that there is a corresponding increase in expenditure of the family with an increase in income. By projecting demand for the occurrence of monocular blindness as a percentage of the population of the National Capital Region, it was determined that there is an increase in demand for eye-drop products in the country. At present, the supply of eye-drops in the market is insufficient to meet projected demand. The project?s computed capacity could address this problem. A marketing strategy was developed to facilitate the introduction of Nature?s Drop in the market. After determining the market feasibility of establishing a manufacturing facility that would produce the herbal eye-drop product Nature?s Drop. With the results of the market study and preliminary information on the manufacture of the product from the inventor, the group developed alternatives as to the technical aspects of the project. This includes the production processes involved, machines and equipment used method of procurement of materials and the method of distribution. These alternatives were evaluated with the primary purpose of improving the current method to adopt it for a small-scale manufacturing setting. In line with this was the selection of a location that would house the facility. Using the criteria such as proximity to materials, market and suppliers favorable labor and geographical climate, utilities rate and the availability of access roads, the group has chosen Bataan among the six other provinces considered. Specifically, the Hermosa Economic Zone is chosen as the plant site because of it being an agro-industrial estate suited for a manufacturing facility for Nature?s Drop. Subsequently, the financial feasibility and the social profitability of the project were determined. The financial feasibility of the study involved the determination of project?s commercial profitability, estimation of the total project cost, evaluation and recommendation of a source of financing for the project. The results of the financial study show that the project is financially feasible. Furthermore, results of the social profitability project prove that the project has a favorable effect in the social and economic conditions of the country.